REFLECTIVE SESSIONS IN KNOWING AND DOING THE SCHOOL PHYSICAL EDUCATION: A PERSPECTIVE FOR SOLIDARITY EDUCATION (Fiep Bulletin - online, 2013)
This article stems on the thesis that developed "Educating for solidarity: a view for school Physical Education", which aimed at to revealing how the knowing to be solidarity has been building in teaching of school Physical Education teachers, in the dynamics of the embodiment, the of seeing, hoping, dialoguing, loving, and embracing and has become the basis for the knowing, doing, living and being supportive. We present the question three of this study this thesis: how the reflexive studies of teachers could set up the knowing to do a school Physical Education from the perspective solidarity? As a methodological approach, we used the collaborative research associated with the History of Life, and among other mediators, we carried out the study seminars and reflective sessions on the laboratory classes with two elementary school teachers in the public network and researcher. A reflective session shows the creation of opportunity for discussion on practical actions of teachers in the classroom and the theories that based. At that point the participants make a critical analysis of these actions in order for processing. The result in this dynamic interactive dynamics in reflective sessions generates learning that, according to Horikawa (2004, p. 142), the teacher translates it in terms of "[...] educational, cultural, social and historical values that are involved in them to redirect their action in an emancipated perspective.
Keywords: Reflective sessions; School Physical Education; Solidarity Education